Water resources development in Africa: a review and synthesis of issues, potentials, and strategies for the future - Rosegrant, Mark W.; Perez, Nicostrato D. (International Food Policy Research Institute, 1997)
This paper analyzes how water resources development and water policy reform can be deployed to address the twin problems of food insecurity and water scarcity in Africa and, in particular, Sub-Saharan Africa. The paper reviews the current status of water supply and demand, and the existing and potential irrigated land base in Africa; reviews the performance of existing irrigation systems and assesses the magnitude of the potential contribution and cost-effectiveness of new irrigation development to future food production in Africa; and explores the potential for water conservation through demand management. Meeting the challenges of food security and water scarcity in Africa will require both selective development and exploitation of new water supplies and comprehensive policy reform that encourages efficient use of existing supplies. The most significant reforms will involve changing the institutional and legal environment in which water is supplied to one that empowers water users to make their own decisions regarding the resource. Irrigation development will not be the main source of food production growth in Africa, but increased investment in irrigation could have an important role in reducing projected cereal import demands. Rehabilitation and improvement of existing irrigation systems can be an attractive option, but projects must be selected carefully.